The "essence" of human subjectivity in the worldview definition as - Bobokulova Khurshida Erkinovna (Global Scientific Publishing, 2022)
In this article, the worldview is defined as a subjective reality, the unchanging essence of the human spiritual being that determines all types of its activities. The definition may not be absolutely perfect in terms of formal logical definitions. Without hereditary and descriptive (species-related) characteristics, we logically consider the elements that are included in the structure of the human worldview from our point of view.
Keywords: worldview; social phenomenon; value; intellectual